Intraspecific Hybridization and Heritability of Biometric and Biochemical Traits in F1 Blueberry (Vaccinium corymbosum L.) Hybrids - Oana Hera; Monica Sturzeanu; Loredana Elena Vijan (Horticulturae)
Blueberry breeding requires a significant commitment of time, skilled labour, and financial resources, but it is essential to develop new cultivars that can meet challenges such as climate change, disease resistance, and changing market preferences. Intraspecific hybridisationis a widely used breeding strategy to increase genetic diversity, broaden the selection base, and develop new cultivars. By crossing different varieties and making advanced selections, breeders can introduce desirable traits such as improved fruit quality, increased yield, improved disease resistance and greater adaptability to environmental conditions. The present study aimed to evaluate the heritability of some key biometric and biochemical parameters inblueberry hybrids derived from intraspecific crosses to assess their inheritance patterns. The results can guide breeders in selecting parent combinations that maximise genetic gain, ultimately supporting the advancement of commercial blueberry production. The ‘Delicia × 4/6’ hybrid combination showed excellent performance for total polyphenol content, flavonoids, tannins, and ascorbic acid, with high genetic gain and near complete heritability, making it a promising candidate for improving antioxidant activity. The ‘Azur × Northblue’ hybrid had favourable total anthocyanin and tannin content, but an unfavourable sugar and ascorbic acid profile.The ‘Simultan × Duke’ hybrid combination showed the highest genetic gain for total soluble solids and firmness, together with high positive heterosis and heterotic progress, highlighting its potential for high-quality cultivars suitable for mechanical harvesting and storage. This research provides valuable insights into the efficiency of intraspecific hybridisationin the development of new blueberry cultivars with improved agronomic and nutritional qualities.